Performance of ILRI-trained high-quality cassava peel (HQCP) mash processors in Nigeria - International Livestock Research Institute (International Livestock Research Institute, 2022)
This video highlights the technical performance of ILRI-trained high-quality cassava peel (HQCP) mash processors in Nigeria.